Physical Activity and Food Frequency in Postmenopausal Women: A Cross-Sectional Study - Homeyra Nournezhad; Saeideh Davar; Davoud Vahabzadeh; Hamideh Mohaddesi; Zahra Sahebazzamani; Atefeh Yas (Mashhad University of Medical Sciences, 2023)
Background & aim: Women spend more than a third of their lives in menopause, and paying attention to their health is one of the most important health issues. The present study was performed to determine the physical activity and food frequency in postmenopausal women.Methods: This cross-sectional study was conducted on 600 postmenopausal women who referred to health centers of Urmia, Iran in 2019. Sampling was performed as multi-stage randomization. To collect data, international physical activity and food frequency questionnaire were used.Results: The mean age of postmenopausal women was 56.64 ± 3.19 years and 93% of them had a body mass index higher than normal. Also, 75% of postmenopausal women had moderate daily physical activity and the average daily physical activity in this group of women was 202.57 ± 135.13 MET. Among the types of physical activities, sports activities had the lowest and working at home had the highest energy consumption. The mean total daily energy intake in postmenopausal women was 3739.80 ± 1251.40 calories, and the consumption of fats, sweets, bread and cereals was more than the standard recommended intake. They had the consumption of dairy products and vegetables less than the need of the body.Conclusion: Postmenopausal women do less daily exercise and use more high-calorie food groups, and their daily energy intake is more than the standard recommended intake.